NUMERICAL ANALYSIS AND ENVIRONMENTAL IMPACT OF AFTERBURNING EXHAUST PLUMES IN ROCKET AND JET ENGINES - Mansoor Ali Khaskheli; Afaque Ahmed Bhutto; K.N. Memon; Mushtaque Hussain; Nabi Bux Kalhoro (Spectrum of Engineering Sciences, 2025)
Rocket exhaust plume dynamics are essential to aerospace propulsion, influencing performance, safety, and environmental impact. After combustion reactions take place because of leftover oxygen in the plume, there is a significant increase in radiation intensity and exhaust gas temperature. This study is intended to examine and assess the improvements in computational modeling and diagnostic methods to comprehend rocket exhaust plume behavior. The focus is on enhancing predictive capabilities, optimizing propulsion system performance, and reducing environmental and operational issues related to plume dynamics. The investigation of rocket exhaust plumes has progressed significantly due to the emergence of high-fidelity Computational Fluid Dynamics approaches like Large Eddy Simulation and Unsteady Reynolds-Averaged Navier-Stokes. These models better the precision of plume flow forecasts by accurately representing turbulence, heat transfer, and intricate chemical interactions. The combination of computational models with cutting-edge diagnostic instruments, especially laser-based methods, has increased the validation of simulation outcomes and refined propulsion system designs. Nonetheless, challenges persist in faithfully depicting extreme thermodynamic situations, evaluating plume-induced structural impacts, and tackling environmental challenges. In addition, research is necessary to advance simulation frameworks, enhance experimental validation, and create sustainable propulsion approaches. Developing these areas will be necessary for designing future aerospace propulsion systems that are both efficient and naturally sustainable.